Lack of age-related differences in temporal lobe volume of very healthy adults. - DeCarli, C; Murphy, D G; Gillette, J A; Haxby, J V; Teichberg, D; Schapiro, M B; Horwitz, B (American Journal of Neuroradiology, 1994)
PURPOSE To evaluate age-related differences in temporal and supratemporal brain regions in carefully selected, very healthy men 19 to 92 years of age. METHODS MR quantification of brain regions used image segmentation into cerebrospinal fluid and brain matter based on nonlinear modeling of pixel intensity distributions. RESULTS There was a significant age-related decrease (approximately 1% per decade) of posterior frontal lobe volume, but not of temporal lobe volume. The mean volume of the right temporal lobe was significantly greater than the left, and this relation did not change with age. CONCLUSION In very healthy aging, the volume of the temporal lobes remains constant over the age range of human life.